Systolic and Diastolic Functions After a Brief Acute Bout of Mild Exercise in Normobaric Hypoxia - Magnani, Sara; Mulliri, Gabriele; Roberto, Silvana; Sechi, Fabio; Ghiani, Giovanna; Sainas, Gianmarco; Nughedu, Giorgio; Vargiu, Romina; Bassareo, Pier Paolo; Crisafulli, Antonio (Frontiers in Physiology, 2021)
Acute hypoxia (AH) is a challenge to the homeostasis of the cardiovascular system, especially during exercise. Research in this area is scarce. We aimed to ascertain whether echocardiographic, Doppler, and tissue Doppler measures were able to detect changes in systolic and diastolic functions during the recovery after exercise in AH. Twelve healthy males (age 33.5 ± 4.8 years) completed a cardiopulmonary test on a electromagnetically braked cycle-ergometer to determine their maximum workload (Wmax). On separate days, participants performed two randomly assigned two exercise sessions consisting in three minutes pedalling at 30% of Wmax: 1) one test was conducted in normoxia (NORMO), and 2) one in normobaric hypoxia with FiO2 set to 13.5% (HYPO). Hemodynamics were assessed with an echocardiographic system. The main result was that the HYPO session increased parameters related to myocardial contractility such as pre-ejection period and systolic myocardial velocity with respect to the NORMO test. Moreover, the HYPO test enhanced early transmitral filling peak velocities. No effects were detected for left ventricular volumes, as end-diastolic, end-systolic, and stroke volume were similar between the NORMO and the HYPO test. Results of the present investigation support the hypothesis that a brief exercise bout in acute normobaric hypoxia does not impair systolic or diastolic functions. Rather, it appears that stroke volume is well preserved and that systolic and early diastolic functions are enhanced by exercise in hypoxia.